Kato nan ampek: Seni berbicara dan etika menghargai dalam budaya Minangkabau - Gustin, Isra Salsabila; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2025)
Kato Nan Ampek is a crucial concept of communication in Minangkabau culture. This concept reflects the art of speaking and respecting others based on context, relationships, and social hierarchy. Each category has specific rules, language styles, and delivery methods that embody the cultural values and social norms of the Minangkabau people. This article examines how Kato Nan Ampek serves as a guideline for maintaining social harmony and demonstrating respect through communication. Furthermore, the study highlights the relevance of Kato Nan Ampek in modern life as a tool to strengthen interpersonal relationships and bridge differences in increasingly diverse societies. By understanding and applying Kato Nan Ampek, individuals can foster more courteous, effective, and culturally grounded interactions.